A comparative study between short term outcome of choledocholithotomy with and without T-tube - Islam, Saoda; Faishal, M.; Hasan, Tarek; Afrin, Sadia; Rahim, Abdur; A. Mamun, Abdullah; Kabir, Z. M. Raihan; Islam, M. Ashraful (International Surgery Journal, 2026)
Background: Management of common bile duct is challenging especially closure of common bile duct (CBD) after removal of stones. The main aim of this study was to find out the outcome of choledocholithotomy with and without tube placement. Methods: This descriptive observational type of study was conducted in the Department of Surgery Sher-E-Bangle Medical College Hospital, Barishal, Bangladesh from December, 2017 to November 2018. A total number of 50 patients were enrolled in the study. The patients were divided into two groups; each group included 25 patients. Group A consisted of the patients who had primary closure while group-B included the patients who had T-tube closure. Results: The mean ages of group A and B were 43.75±2.76 (range: 29-63) years and 45.77±3.19 (range: 28-69) years respectively. Most of the patients were male in both groups (72% versus 80%). Diabetes mellitus was the major co-morbidity in both groups (32% versus 28%). Mean operating time significantly higher in open choledocholithotomy with T-tube insertion than open choledocholithotomy with primary closure (p=0.001). Additionally, mean hospital stay was also longer in T-tube insertion group rather than primary closure group which statistically the difference was significant (p=0.001). Wound infection (16% versus 36%) biliary fistula (4% versus 20%) subphrenic abscess (2% versus 0%), biliary leakage (4% versus 12%), jaundice % versus 8%) and retained stone (0% versus 4%) were the observed complications in primary closure group and t-tube closure group patients respectively. Postoperative complications were relatively higher in t-tube closure group though it was not statistically significant (p≥0.05). Conclusions: Both primary closure of CBD and T-tube drainage after CBD exploration are equally good procedures for the treatment of uncomplicated choledocholithiasis. However, primary closure of CBD is having significantly lower operating time and less duration of stay at hospital.